CLONING OF FLOWERING GENES (WJFLC AND WJFT) IN WASABI (JAPANESE HORSERADISH) AND MONITORING OF FLOWERING RESPONSE WITH THEIR EXPRESSION - Masayuki Nozue; Hiroyoshi Kubo; Kiyoshi Yoshida (Central Laboratory for Genetic Resource and Molecular Biology, Faculty of Agriculture, Udayana University in cooperation with Asia-Oceania Bioscience and Biotechnology Consortium (AOBBC), 2013)
Wasabi (Wasabia japonica) is a commercially important crop in Japan. We isolated a FLC ortholog (WjFLC)and FT ortholog (WjFT) from wasabi. Predicted amino acid sequence encoded by WjFLC and WjFT showed89% and 85% identities with FLC and FT of Arabidopsis, respectively. The expression of WjFLC was high inOctober and reduced in November when fl ower buds are formed in wasabi. On the other hand, expressionof WjFT was not detected in October and was slightly detected in November. Thereafter, WjFT was highlyexpressed later in February. We examined the best condition for initiation of fl ower bud formation undervarious artifi cial environments by monitoring the fl owering response of wasabi using WjFLC and WjFT.